2017
DOI: 10.1186/s12978-017-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcomes following obstetric fistula repair: a prospective cohort study

Abstract: BackgroundObstetric fistula (OF) is a maternal morbidity associated with high rates of stillbirth, amenorrhea, and sexual dysfunction. Limited data exists on the reproductive outcomes of women in the years following a fistula repair. The objective of this study is to describe the fertility outcomes and family planning practices in a population of Malawian women 1–4 years after fistula repair.MethodsWomen who had enrolled into a clinical database of OF patients and undergone OF repair between January 1, 2012 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…They may require further medical care depending on injury severity and surgical outcomes, and medical support for subsequent pregnancies and births. Longitudinal studies from sub‐Saharan Africa have identified concerning adversity following fistula surgery, including fistula recurrence, persistent fistula‐related symptoms, subsequent fertility challenges, and adverse perinatal outcomes . In Guinea, 16% experienced fistula recurrence by 24 months .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may require further medical care depending on injury severity and surgical outcomes, and medical support for subsequent pregnancies and births. Longitudinal studies from sub‐Saharan Africa have identified concerning adversity following fistula surgery, including fistula recurrence, persistent fistula‐related symptoms, subsequent fertility challenges, and adverse perinatal outcomes . In Guinea, 16% experienced fistula recurrence by 24 months .…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, by 12 months following repair, one‐third had persistent urinary incontinence, 17% weakness, and 9% general pain . In Malawi, only one‐fifth of women with reproductive potential became pregnant in the year following surgery . Experience of persistent physical adversity correlates with substantially lower psychosocial health .…”
Section: Introductionmentioning
confidence: 99%
“…A surgical approach is contemplated the mainstay and definitive management of the VUF following caesarean section [ 17 ]. Notably, a subset of women was able to resume a normal period after fistula repair [ 14 ], though the data on how frequently this occurs is very limited [ 2 , 10 , 14 ]. Due to the low prevalence of VUF, although hysterectomy is not obligatory, it is not easy to find the most assuring approach to manage VUF.…”
Section: Discussionmentioning
confidence: 99%
“…They may also require further medical care depending on the severity of their injuries and surgical outcomes and require healthcare access for subsequent pregnancies and births. Longitudinal studies from sub-Saharan Africa have identified risks of adverse outcome following fistula surgery, including fistula recurrence, persistent fistula-related symptoms, subsequent fertility challenges and adverse perinatal outcomes 11–13. In Guinea, for example, the cumulative incidence of fistula recurrence was 16% at 24 months13.…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, by 12 months postsurgery, one-third of women continued to experience urinary incontinence, 17% reported weakness and 9% reported general pain 14. In Malawi, only one-fifth of women with reproductive potential were able to become pregnant in the year following surgery 12. Furthermore, experience of persistent physical symptoms or adversity is associated with substantially lower psychosocial health 14.…”
Section: Introductionmentioning
confidence: 99%